2012
DOI: 10.2527/jas.2010-3470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress associated with weaning on the adaptive immune system in pigs1

Abstract: This study was designed to investigate the effects of weaning age on specific components of the adaptive immune system in pigs. Twenty-three crossbred pigs were randomly assigned to 1 of 3 treatments: weaning at 14 (14D, n = 8), 21 (21D, n = 7), or 28 (28D, n = 8) d of age. Peripheral blood samples, obtained when pigs were 13, 15, 20, 22, 27, 29, and 35 d of age, were analyzed for peripheral blood cell percentages and concentrations of neutrophils, lymphocytes, T cell subsets, mature B cells, and plasma cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…Previous studies have demonstrated that chronic stress dysregulated the immune response by weakening the responses of lymphocytes to mitogens (Silberman et al, 2002), decreasing the T helper/T suppressor cell ratio (Segerstrom & Miller, 2004), and disturbing the balance of Th1/Th2 cells (Dhabhar, 2009). The down-regulation of the CD4 + T/CD8 + T cell ratio is accompanied by abnormal behavior (Stefanski et al, 2005), body weight loss (Kick et al, 2012), and the abnormal distribution of blastocysts (Wongweragiat et al, 1999). In the present study, restraint stress decreased the proliferative activities of uterine lymphocytes, and the CD3 + CD4 + T/CD3 + CD8 + T cell ratio.…”
Section: Restraint Stress Altered Local Uterine Immune Activitymentioning
confidence: 85%
“…Previous studies have demonstrated that chronic stress dysregulated the immune response by weakening the responses of lymphocytes to mitogens (Silberman et al, 2002), decreasing the T helper/T suppressor cell ratio (Segerstrom & Miller, 2004), and disturbing the balance of Th1/Th2 cells (Dhabhar, 2009). The down-regulation of the CD4 + T/CD8 + T cell ratio is accompanied by abnormal behavior (Stefanski et al, 2005), body weight loss (Kick et al, 2012), and the abnormal distribution of blastocysts (Wongweragiat et al, 1999). In the present study, restraint stress decreased the proliferative activities of uterine lymphocytes, and the CD3 + CD4 + T/CD3 + CD8 + T cell ratio.…”
Section: Restraint Stress Altered Local Uterine Immune Activitymentioning
confidence: 85%
“…Moreover, in order to avoid the transitional trapping lymphocytes effects of weaning on immune system [38], last day of experiment was performed on day 19, two days after early weaning.…”
Section: Methodsmentioning
confidence: 99%
“…Sugiharto et al (2014) reported that the concentration of plasma IgA was higher on day 11 than on days 0 and 4 postweaning, with no significant changes in IgG levels. However, Kick et al (2012) demonstrated that early weaning did not negatively affect the adaptive immunological competence of piglets. Our results showed that the concentrations of IgA, IgG, and IgM did not significantly change during the first week post-weaning; however, IgA levels had a decreasing trend with increasing weaning time.…”
Section: Discussionmentioning
confidence: 99%